Intravitreal injection of Huperzine A promotes retinal ganglion cells survival and axonal regeneration after optic nerve crush - Zhou, Lai-Yang; Chen, Di; Guo, Xin-Ran; Niu, Yu-Qian; Xu, Yong-Sai; Feng, Dong-Fu; Li, Tie-Chen (Frontiers in Cellular Neuroscience, 2023)
Traumatic optic neuropathy (TON) is a condition that causes massive loss of retinal ganglion cells (RGCs) and their axonal fibers, leading to visual insufficiency. Several intrinsic and external factors can limit the regenerative ability of RGC after TON, subsequently resulting in RGC death. Hence, it is important to investigate a potential drug that can protect RGC after TON and enhance its regenerative capacity. Herein, we investigated whether Huperzine A (HupA), extracted from a Chinese herb, has neuroprotective effects and may enhance neuronal regeneration following the optic nerve crush (ONC) model. We compared the three modes of drug delivery and found that intravitreal injection of HupA could promote RGC survival and axonal regeneration after ONC. Mechanistically, HupA exerted its neuroprotective and axonal regenerative effects through the mTOR pathway; these effects could be blocked by rapamycin. To sum up, our findings suggest a promising application of HupA in the clinical treatment of traumatic optic nerve.